Diversity of Free Living Nematodes Under Agriculture Farming System in Kathmandu Valley - Bagale, Narayan; Dhakal, Ankita (Journal of Multidisciplinary Research Advancements, 2025)
This study investigated the diversity and community composition of soil nematodes in tomato-growing farms across the Kathmandu Valley, Nepal. Fifty-four soil samples were collected from rhizospheres in three districts (Kathmandu, Bhaktapur, Lalitpur), revealing 14 families across five orders. Herbivorous nematodes dominated the community, followed by bacterivores, fungivores, omnivores, and predators. Ecological indices such as the Maturity Index (MI), Plant Parasitic Index (PPI), and Enrichment Index (EI) indicated varying levels of soil disturbance and fertility. The results underscore the role of nematodes as indicators of soil health and highlight the need for sustainable farming practices to maintain soil biodiversity.